Impact of Physical Inactivity on Subcutaneous Adipose Tissue Metabolism in Healthy Young Male Offspring of Patients With Type 2 Diabetes - Højbjerre, Lise (American Diabetes Association, 2010)
OBJECTIVE: Physical inactivity is a risk factor for type 2 diabetes and may be more detrimental in first-degree relative (FDR) subjects, unmasking underlying defects of metabolism. Using a positive family history of type 2 diabetes as a marker of increased genetic risk, the aim of this study was to investigate the impact of physical inactivity on adipose tissue (AT) metabolism in FDR subjects. RESEARCH DESIGN AND METHODS: A total of 13 FDR and 20 control (CON) subjects participated in the study. All were studied before and after 10 days of bed rest using the glucose clamp technique combined with measurements of glucose uptake, lipolysis, and lactate release from subcutaneous abdominal (SCAAT) and femoral (SCFAT) adipose tissue by the microdialysis technique. Additionally, mRNA expression of lipases was determined in biopsies from SCAAT. RESULTS: Before bed rest, the FDR subjects revealed significantly increased glucose uptake in SCAAT. Furthermore, mRNA expression of lipases was significantly decreased in the SCAAT of FDR subjects. Bed rest significantly decreased lipolysis and tended to increase glucose uptake in the SCFAT of both CON and FDR subjects. In response to bed rest, SCAAT glucose uptake significantly increased in CON subjects but not in FDR subjects. CONCLUSIONS: FDR subjects exhibit an abnormal AT metabolism including increased glucose uptake prior to bed rest. However, the differences between FDR and CON subjects in AT metabolism were attenuated during bed rest due to relatively more adverse changes in CON subjects compared with FDR subjects. Physical inactivity per se is not more deleterious in FDR subjects as compared with CON subjects with respect to derangements in AT metabolism.